Peer Trust as a Mediator Between Learning Organization Culture and Innovative Behavior Among Faculty - Honkley, Tony; Banuari, Nidya; Tandeas, William (Journal of Business Integration Competitive, 2025)
This study explores the role of peer trust in mediating the relationship between learning organization and innovative work behavior among permanent lecturers at Universitas Mahkota Tricom Unggul. Using a quantitative approach, data was collected from 51 lecturers through structured questionnaires and analyzed using Structural Equation Modeling (SEM). The results show that both learning organization and peer trust significantly influence innovative work behavior. Peer trust is identified as a key mediator, with its indirect effects being stronger than direct ones. This highlights the importance of interpersonal trust in promoting innovative behavior. The study contributes to the literature on organizational behavior and innovation in higher education by emphasizing the role of peer trust. It also enhances understanding of how organizational culture and trust among colleagues foster innovation. The findings suggest that universities should cultivate a supportive organizational culture and peer trust to encourage innovative work behavior. However, the study is limited to a single institution, and its findings may not be applicable to other universities. Future research should examine the role of peer trust in broader contexts within higher education institutions.